PERGESERAN STRUKTUR PEREKONOMIAN DI KABUPATEN MINAHASA UTARA (The Shifting of Economic Structure in North Minahasa Regency) - David J. V. Lolos; Caroline B. D. Pakasi; Celsius Talumingan (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2020)
North Minahasa is one of the regencies which is located between two big cities, namely Bitung City and Manado City. The development that is happening in Bitung City will affect  North Minahasa Regency and also the development in Manado city will affect  North Minahasa Regency. The current development  is the construction of the toll road connecting Manado and Bitung. This development increases the development in North Minahasa Regency and changes its economic development. North Minahasa Regency has 10 sub-districts with an area of 1,059.24 Km and has a growing potential because it is located between Bitung City and Manado City,therefore it has a very big influence and affects the trade sector of North Minahasa Regency. Sectors which are non-base sectors during the period of 2014-2018 are 10 sectors, namely  Water Supply, Waste Management, Waste and Recycling sectors with an average LQ of 0.59, the Wholesale and Retail Trade sector, Car and Motorcycle Repair Repairs of the LQ an average of 0.77, the LQ Transport and Warehousing sector averaged 0.48, the accommodation and Food and Drinking LQ sector averaged 0.49, the LQ Information and Communication sector averaged 0.45, the LQ Financial Services and Insurance sector 0, 23, the LQ Company Services sector an average of 0.18, the Government Administration, Defense and Compulsory Social Security LQ sector averaged 0.50, the Health Services and Social Activities sector an average of 0.68, the Other Services sector LQ average of 0.35.Keywords: Shifting of Economic Structures